2010
DOI: 10.1021/ic101355d
|View full text |Cite
|
Sign up to set email alerts
|

First Ruthenium Organometallic Complex of Antibacterial Agent Ofloxacin. Crystal Structure and Interactions with DNA

Abstract: Organometallic ruthenium complex of quinolone antibacterial agent ofloxacin [(η6-p-cymene)RuCl(O,O-oflo)]·2.8H2O (1·2.8H2O) was isolated and its crystal structure was determined. In this »piano-stool« complex, quinolone is bidentately coordinated to the metal through the ring carbonyl and one of the carboxylic oxygen atoms. Interactions of the title complex with DNA were studied by spectroscopic methods (electronic, fluorescence, CD) and atomic force microscopy (AFM). It was established that the electrostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 20 publications
1
79
1
2
Order By: Relevance
“…Complexes 1-3 exhibited higher inhibitory effects than ofloxacin at the same concentrations of 50 and 100 μM. Moreover, 3 exhibited the best inhibition, which indicated that increasing of the aromatic ring can enhance the antitumor activity of Ru(II) complexes [27][28][29].…”
Section: Studies On the Antitumor Activitiesmentioning
confidence: 91%
“…Complexes 1-3 exhibited higher inhibitory effects than ofloxacin at the same concentrations of 50 and 100 μM. Moreover, 3 exhibited the best inhibition, which indicated that increasing of the aromatic ring can enhance the antitumor activity of Ru(II) complexes [27][28][29].…”
Section: Studies On the Antitumor Activitiesmentioning
confidence: 91%
“…3 In contrast, some organometallic compounds are evaluated as chemotherapeutics for a number of diseases, such as cancer 8 and malaria, 9 and are therefore, considered as potential antimicrobial agents. [10][11][12][13][14] Synthetic organometallic antimicrobial agents are structurally unique, leading to new mechanism of action that bypass resistance mechanism, ultimately resulting in potent activity against multidrug-resistant microbes. Regrettably, research on this class of antimicrobial is still at the early stage, 15 focusing 4 on small molecules or conventional macromolecular scaffolds, 11 and consequently, the unexplored potential of this class still needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Since the main targets of quinolones are the enzymes gyrase (type II topoisomerases) and topoisomerase IV participating in the DNA replication [4], the interaction with DNA and the antibacterial activity tested on diverse microorganisms are of great importance and thoroughly studied [5]. Based on the increased activity shown by metal complexes of drugs in comparison to their parent compounds [6], diverse metal complexes with quinolones as ligands have been synthesized and characterized and the interaction with DNA [7][8][9][10] and serum albumin proteins [11][12][13][14], the antibacterial activity [15][16][17], and the potential antitumor activity [18][19][20] have been evaluated in comparison to free quinolones.…”
Section: Introductionmentioning
confidence: 99%